Implementasi Pendidikan Agama Islam Dalam Pengamalan Ibadah Siswa di SD Negeri 03 Teras Terunjam Kabupaten Muko-Muko Provinsi Bengkulu Tahun Ajaran 2021/2022 - Fitriyanti Nurhasanah; Irwan Satria; Masrifa Hidayani (Yayasan Darussalam Bengkulu, 2025)
The purpose of this study is to determine the implementation of Islamic Religious Education in practicing student worship at SD Negeri 03 Teras Terunjam, Muko-Muko Regency, Bengkulu Province, Academic Year 2021/2022, To determine the supporting or inhibiting factors of the Implementation of Islamic Religious Education in the Practice of Student Worship at D Negeri 03 Teras Terunjam, Muko-Muko Regency, Bengkulu Province, Academic Year 2021/2022. The key informants are the principal, curriculum vice principal, and Islamic religious education teacher, Additional informants are 5th grade students. To collect the necessary data, the author uses interviews, documentation and observation. The results of the research are the Implementation of Islamic Religious Education Learning at SD Negeri 03 Teras Terunjam, Muko-Muko Regency, Bengkulu Province, in the 2021/2022 Academic Year, has been carried out well, the teachers carry out learning in the classroom by using habituation methods and compiling lesson plans to create good morals so that they can practice the worship they get, The practice of student worship at SD Negeri 03 Teras Terunjam, Muko-Muko Regency, Bengkulu Province, in the 2021/2022 Academic Year by applying good manners, reading prayers before carrying out activities and performing prayers on time.